Quantitative immunhistochemische Untersuchung der Innervation der Koronararterien der Ratte - Sequeira, Indira Maria; Justus Liebig University Giessen (My University, 2005)
Die Regulation des koronaren Blutflusses wird durch viele Faktoren und Mechanismen bestimmt. Eingeschlossen sind hier metabolische und myogene Faktoren, endotheliale und humorale Mechanismen sowie die Modifikation des Gefäßtonus durch perivaskuläre Nervenfasern. Die Bedeutung dieser neuronalen Steuerung ist organspezifisch und korreliert mit der Innervationsdichte. Quantitative Untersuchungen zur perivaskulären Innervationsdichte liegen nur für wenige Organe vor und fehlen für die koronare Strombahn. Daher wurden in der vorliegenden Studie die cholinerge Innervation (VAChT-immunreaktiv), die noradrenerge sympathische Innervation (TH-immunreaktiv), die viszerosensible Innervation (CGRP-immunreaktiv) und die Innervation durch NO-produzierende Axone der Koronararterien der Ratte immunhistochemisch dargestellt. Das Herz wurde hierbei in drei Abschnitte unterteilt: A) Vorhof, B) vorhofnaher Ventrikel; C) Herzspitze. Jeweils die Gefäße von zwei Querschnitten, welche einen Abstand von 200 µm zueinander hatten, wurden für den einzelnen Herzabschnitt ausgewertet. Die Arterien wurden erfasst, mit Hilfe der an das Mikroskop angeschlossenen Digitalkamera als Bilddatei im Computer gespeichert und die Innervation wurde quantitativ auf den inneren Gefäßdurchmesser bezogen ermittelt. Als Maß für die Innervationsdichte wurde der Innervationsindex eingeführt. Er umfasst denjenigen Anteil in Prozent vom Gesamtumfang eines Gefäßes, welcher von immunreaktiven Nervenfasern umgeben ist. Die vorliegende Studie zeigt, dass mit Ausnahme der NO-produzierenden Axone alle hier untersuchen Nervenfasertypen in allen Herzabschnitten arterielle Gefäße innervieren. NO-produzierende Axone konnten nur in Gefäßen des Vorhofs dargestellt werden. Es zeigten sich signifikante Unterschiede zwischen den Innervationsindices der cholinergen und der noradrenergen sympathischen Nervenfasern auf der einen Seite und der viszerosensiblen Nervenfasern auf der anderen Seite. Während für die Größe des Innervationsindex für CGRP in allen Abschnitten des Herzens kein signifikanter Unterschied gezeigt werden konnte und auch keine Korrelation zur Gefäßgröße zu sehen war, waren die Innervationsindices für VAChT und TH in den Vorhöfen signifikant größer als in den Ventrikeln. Weiterhin konnte in jeweils zwei von drei Herzabschnitten eine negative Korrelation zwischen der Gefäßgröße und dem Innervationsindex für VAChT und TH gezeigt werden. Noradrenerge sympathische perivaskuläre Nervenfasern sind im Ventrikel signifikant stärker vertreten als cholinerge und viszerosensible Nervenfasern. Nur im Vorhof ist der Innervationsindex für VAChT signifikant größer als der für CGRP. In den Ventrikeln zeigt sich diesbezüglich kein signifikanter Unterschied. Die Ergebnisse der vorliegenden Studie implizieren, dass die Regulation des Blutflusses auf der Vorhofebene stärker neuronal gesteuert wird als in den Ventrikeln. Weiterhin konnte im Gegensatz zu Untersuchungen an der Lunge und der Zunge gezeigt werden, dass die kleinen Gefäße des Herzens stärker perivaskulär autonom innerviert werden als die größeren Gefäße. Daraus lässt sich schließen, dass hier über eine Regulation des Tonus insbesondere der Widerstandsgefäße der koronare Blutfluss entscheidend mitreguliert wird. Die nur geringe perivaskuläre Innervation durch NO-enthaltende Axone lässt den Schluss zu, dass im Gegensatz zur großen Bedeutung von endothelial gebildetem NO das perivaskuläre freigesetzte NO in der koronaren Strombahn eine eher untergeordnete Rolle spielt. Die vorliegende Studie zeigt eine homogene Verteilung von CGRP-enthaltenden perivaskulären viszerosensiblen Nervenfasern. Diese gewährleistet in allen Herzregionen gleichmäßig die Nozizeption und durch die lokale Effektorfunktion eine Einleitung der hypoxischen Präkonditionierung. Zusammenfassend zeigt die vorliegende Studie, dass die koronare Strombahn in allen Herzabschnitten, besonders aber im Vorhof, eine erhebliche perivaskuläre Innervation aufweist und impliziert damit eine große Bedeutung bei der Regulation des koronaren Blutflusses.

Arterial tone is under control of multiple determinants including circulating hormones, endothelial-derived factors, metabolic factors originating from the surrounding tissue and perivascular nerve fibers. The relative contribution of the perivascular nerves is highly specific for individual organs and vascular beds, and correlates with the extent of the perivascular innervation. Quantitative immunhistochemical investigations on vascular innervation are only available for a limited number of organs and are missing for the coronary circulation. Hence, in the present immunohistochemical study set out to determine the extent of perivascular innervation in the rat heart. Sympathetic noradrenergic axons were visualized by an antiserum against the rate-limiting enzyme of catecholamine synthesis, tyrosine hydroxylase (TH). Parasympathetic cholinergic axons were labelled with an antiserum against the vesicular acetylcholine transporter (VAChT). Also, an antiserum against the neuronal isoform of the nitric oxide synthase (nNOS) was used in this study. Viscerosensory axons were visualized by aid of an antiserum against calcitonin gene-related peptide (CGRP). For each of these antigens, the innervation density of arteries and arterioles was assed separately in A) the atria, B) the basal and C) the apical parts of the ventricles. Evaluation was performed in each specimen on 2 sections being 200 µm apart in depth. Images obtained from an epifluorescence microscope were captured with a digital camera and evaluated with Scion image software. For each of the cardiac regions, the 'index of innervation', defined as that part (in percent) of the arterial circumference that was covered with immunoreactive nerve fibres, was plotted against the inner vascular diameter. The present study showed that VAChT, TH, and CGRP containing perivascular fibres occur in each part of the rat heart. In contrast, nNOS containing perivascular fibres are present only in the atria. Significant differences were observed between the index of innervation for TH-immunoreactive fibres and VAChT-immunoreactive fibres on the one hand and CGRP-immunoreactive perivascular fibres on the other hand. While there was neither a significant difference of the index of innervation for CGRP between the different heart regions and nor a significant correlation between vascular diameter and index of innervation for CGRP, there was a significantly higher index of innervation for TH- and VAChT-immunoreactive axons detected in the atria in comparison to the ventricles. Furthermore, in two of the three parts of the heart a negative linear correlation between index of innervation and vascular diameter was observed for TH- and VAChT-immunoreactive perivascular fibres. In both parts of the ventricles, there was a significantly higher index of innervation for TH-immunoreactive axons when compared with VAChT- and CGRP-immunreactive fibres. Only in the atrial myocardium arteries were more densely innervated by VAChT-immunreactive fibres than by CGRP-immunreactive fibres, while there was no difference noted in both parts of the ventricle. The results of the present study indicate that the role of neural regulation on coronary blood flow is higher in the atrial myocardium than in the myocardium of the ventricle. In contrast to results of investigations of the lung and tongue the present study demonstrates a higher perivascular innervation by parasympathetic cholinergic axons and sympathetic noradrenergic axons of small vessels compared with vessels with large diameters. This distribution indicates a dominating role of neural regulation on the coronary blood flow at the level of resistance vessels. The present study showed that perivascular axons with immunoreactivity against nNOS are very sparse. This result indicates that the nitrergic component involved in the regulation of coronary blood flow originate from the endothelium rather then nerve endings. CGRP-immunoreactive perivascular fibres equally supply all parts of the coronary arterial tree. The described distribution pattern for CGRP-immunoreactive perivascular fibres ensure a homogeneous sensory system and it contributes to cardioprotection against ischemia-reperfusion injury. Collectively, the present study shows that especially the atrial vessels are dense innervated by perivascular nerves. The findings indicate that perivascular nerve fibres strongly influence arterial tone.
Keywords: Perivaskuläre Innervation; Koronararterien; Immunhistochemie; Ratte; ddc:610